Nilai Pendidikan Sosial Kemasyarakatan dalam Kisah Nabi Ismail A.S Perspektif Sejarah - Imran Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
One of the stories that Allah has immortalized in the Qur'an is the story of the Prophet Ismail a.s. Prophet Isma'il a.s is the son of Prophet Ibrahim a.s and Siti Hajar. The test of faith that Ismail received to carry out the slaughter was a form of Ismail's obedience to his parents. The foundation of faith and belief gives birth to individuals who are able and willing to sacrifice various interests including their lives for service. This shows how high the morals and manners of the child are and with the words of Prophet Ismail a.s, it can also be solace in the face of exams. The condition and attitude of the child in this verse are also an indication of the success of an education implanted in the household. The value of social education, which is stated in the story of the Prophet Isma'il a.s. One of them is when the Zamzam spring appears, instinctively the birds begin to approach and gather around it and the travelers begin to stop to quench their thirst. Some of them even asked permission to set up a tent or a place to live there. It was this tolerant attitude that caused Siti Hajar and Prophet Isma'il a.s to have high social spirits.